Rare esophageal ulcers related to Behçet disease: A case report. Issue 44 (November 2017) - Jia, Ning; Tang, Yanping; Liu, Huayi; Li, Yang; Liu, Simiao; Liu, Lei
Abstract: Rationale: The fundamental pathogenesis of Behçet disease (BD) is still unclear and controversial. Many cases of oral aphthous ulcers and genital ulcers related to BD are reported; nevertheless, idiopathic giant esophageal ulcers related to BD are rare. A rare case for esophageal ulcers related to BD is presented. Patient concerns: In China, BD is represented with esophageal involvement which is called esophageal BD (EBD). Diagnoses: A 56-year-old man diagnosed to the Gastroenterology Department of Integrated Traditional Chinese and Western Medicine Hospital, for multiple discrete, elliptical esophageal ulcers related to BD. Interventions: The esophageal ulcers were treated with corticosteroid treatment for 12 weeks. Outcome: The esophageal ulcers were cured. Lessons: Our report might give further strength to avoiding the erroneous diagnosis or missed diagnosis for EBD, which is different from esophageal carcinoma, esophageal tuberculosis and esophageal Crohns disease.